A novel RHCE*ce 48C, 733G allele with nucleotide 941C in exon 7, encodes an altered red cell e antigen - Hue-Roye, Kim (2011)
BACKGROUND: Several RHCE*ce alleles have in common a 733C>G (Leu245Val) change. Some encode an altered expression of e on RBCs and individuals with such RBCs can make e-like alloantibodies. The identification of an apparent anti-hr(B) in the serum of an E–e+ African American patient prompted us to analyze her DNA, which revealed a novel RHCE*ce allele. We also screened blood samples from African Americans to determine the frequency of the novel allele. METHODS: Hemagglutination tests and molecular analyses were performed by standard procedures. RESULTS: Analysis of the proband’s DNA revealed RHCE*ce 48C/C, 733G/G, 941T/C, and 1006G/T. Of 272 samples from African Americans, 257 were RHCE*941T/T (wild type), and 15 (6%) were RHCE*941T/C. Of these 15, 14 were RHCE*ce/ce; ten with 733C/G, and four with 733G/G; and one was RHCE*ce/cE, 733C/G. Cloning experiments confirmed the nucleotide 941 change and showed that 48C, 733G, and 941C were carried on the same allele. RBCs from the 15 samples carrying the RHCE*941C variant typed V/VS+ and hr(B)+(W). CONCLUSION: This study identifies a novel allele, RHCE*ce 48C, 733G, 941C, which is predicted to encode 16Cys, 245Val, and 314Ala and was shown to encode c, V/VS, and an altered expression of e and hr(B) antigens. The clinical significance of the antibody found in the proband is not established because E+e– RBC components were transfused to the patient. The novel RHCE*ce 48C, 733G, 941C allele was present in 5.5% of samples from African Americans and thus, in this small cohort, it had a frequency of 0.028.